Strategi Komunikasi Dai Muda dalam Menyebarkan Pesan Dakwah di Tiktok - Andayani, Rinni Dwi; Rahma, Khalisya; Razzaq, Abdur; Nugraha, Muhamad Yudistira (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
The development of digital technology, especially social media such as Tiktok, has opened up new space for the spread of Islamic preaching messages. This article discusses the communication strategies used by young preachers in delivering preaching through the Tiktok platform. This study uses a descriptive qualitative approach with case studies on several accounts of young preachers who are actively preaching on Tiktok. The results of the study show that young preachers utilize creativity in the form of delivering content that is short, interesting, and relevant to current issues. They also use communicative language and attractive visuals to reach the younger generation. Other strategies implemented include consistency in uploads, active interaction with followers, and the use of Tiktok trends and features such as music, filters, and hashtags to increase the reach of preaching. With this research, young preachers are able to convey Islamic values ​​effectively and are accepted by a wider audience, especially teenagers and millennials. This study concludes that the success of young preachers in preaching on Tiktok is greatly influenced by their ability to adapt communication strategies in a dynamic and rapidly changing digital context. This finding emphasizes the importance of digital competence for young preachers in facing the challenges of preaching in the modern era, as well as the need for a creative and contextual approach so that Islamic preaching remains relevant and touches the hearts of the wider community, especially the younger generation.